Return-to-work rates and predictors of absence duration after COVID-19 over the course of the pandemic - Bart Aben; Robin N Kok; Astrid de Wind (Nordic Association of Occupational Safety and Health (NOROSH), 2023)
OBJECTIVES: The aim of this study was to evaluate employee return-to-work (RTW) rates and examine predictors of absence duration after COVID-19. RTW rates were referenced against RTW rates after absence due to flu-like symptoms and assessed over the course of the pandemic.METHODS: Routinely collected data from a nationally operating Dutch occupational health service was used. The data were retrieved from employees who reported sick due to COVID-19 (N=30 396) or flu-like symptoms (N=15 862). Data consisted of responses to a triage survey combined with longitudinal register-based information on sickness absence. RTW rates after COVID-19 were evaluated through Kaplan-Meier estimates and compared to RTW rates for flu-like symptoms, and between three periods with different dominant virus variants. Predictors for absence duration were examined through Cox proportional hazards models.RESULTS: RTW after COVID-19 was found to be notably later than after flu-like symptoms (median RTW=10 versus 6 days, respectively). On average, 5.5% of employees who contracted COVID-19 were absent for over 12 weeks. Time-to-RTW shortened as different virus variants became dominant over time. The main predictors contributing to later RTW were older age, female sex, belonging to a risk group, and the symptoms shortness of breath and fatigue.CONCLUSIONS: Estimates of the RTW rate after COVID-19 and identification of predictors may aid healthcare professionals in gaining insight into variations in the disease course and rehabilitation process. The present findings can help employers and policy-makers grasp the impact of COVID-19 on the workplace.